2004
DOI: 10.1038/sj.gt.3302416
|View full text |Cite|
|
Sign up to set email alerts
|

VEGF165 and angiopoietin-1 decreased myocardium infarct size through phosphatidylinositol-3 kinase and Bcl-2 pathways

Abstract: Angiogenic growth factors, vascular endothelial growth factor (VEGF) and angiopoietin-1 (Ang1) could decrease myocardial infarct size, which was assumed to be related with newly formed capillaries. We doubted that these capillaries could do this solely and the potential protective mechanisms of VEGF and Ang1 on myocardium need to be evaluated. Three types of adenoviruses encoding human VEGF 165 (Ad-VEGF 165 ), human angiopoietin-1 (Ad-Ang1) and green fluorescent protein (Ad-GFP, as a parallel control) were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…We have shown in previous publications that overexpression of VEGF and Ang1 improves cardiac function in mouse and rat MI heart models through their angiogenic and antiapoptotic functions (4,15). Here, we have showed that VEGF/Ang1 induced neovascular formation and reduced myocardial apoptosis in infarct and peri-infarct zones of porcine acute MI heart.…”
Section: Discussionmentioning
confidence: 50%
“…We have shown in previous publications that overexpression of VEGF and Ang1 improves cardiac function in mouse and rat MI heart models through their angiogenic and antiapoptotic functions (4,15). Here, we have showed that VEGF/Ang1 induced neovascular formation and reduced myocardial apoptosis in infarct and peri-infarct zones of porcine acute MI heart.…”
Section: Discussionmentioning
confidence: 50%
“…This report points out that enhanced level of VEGF may have some role in the inhibition of cardiomyocyte and endothelial cell apoptosis. VEGF could activate the myocardial PI-3K pathway and decrease myocardial infarct size [27]. Basic fibroblast growth factor also plays an important role in cardioprotection against myocardial cell death and arrhythmias in acute myocardial infarction (AMI).…”
Section: Discussionmentioning
confidence: 99%
“…65 Several strategies to enhance myocardial angiogenesis have been investigated, including delivery of angiogenic genes or growth factors. The candidate angiogenic factors include VEGF-A, [66][67][68][69] 69,82 and porcine 83 models of MI. A combination of fibroblast growth factor-2 and hepatocyte growth factor synergistically stimulated angiogenesis and prevented progression of heart failure in a rat model of MI.…”
Section: Therapeutic Myocardial Angiogenesis As a Potential Therapy Fmentioning
confidence: 99%